Biological properties of a benzothiazole-based mononuclear platinum(II) complex as a potential anticancer agent. Issue 12 (17th June 2020) - Chen, Zhanfen; Wu, Yixuan; Zhang, Qiang; Zhang, Yumin
Abstract: A mononuclear platinum(II) complex, [PtL Cl]Cl (1, where L = N -(4-(benzo[ d ]thiazol-2-yl)phenyl)-2-(bis(pyridine-2-ylmethyl)-amino)acetamide), was synthesized by covalently tethering a benzothiazole derivative 2-(4-aminophenyl)benzothiazole to the 2, 2′-dipicolylamine (DPA) chelating Pt II center by an amidic bond. 1 showed a cytotoxicity comparable to that of cisplatin against MCF-7 cell lines and more potent activities against HeLa and A-549 cell lines. Investigation of the reaction of 1 with 5′-GMP displayed 1 could coordinate with N7-GMP to form the Pt-GMP adduct. Thus 1 has potential to form Pt-DNA adducts in vivo . Similarly, the glutathione (GSH) ligand could also coordinate to the Pt II center to form a monodentate Pt-GS complex. The competition experiments of 1 with 5′-GMP and GSH showed that the coordination binding of 1 with GSH did not prevent formation of a certain amount of the Pt-GMP adduct in the reaction process. DNA binding experiments displayed that 1 could bind to DNA through multiple binding modes involving non-covalent interaction and monofunctional platination of the platinum(II) moiety, and induce a visible conformational change of DNA. The evaluation of the protein binding ability showed that 1 could bind to human serum albumin (HSA) with a moderate binding affinity, quench the intrinsic fluorescence of HSA, and destroy the tertiary structure of HSA. Abstract :